Relationship of parathyroid adenoma volume with preoperative biochemical parameters - Özçelik, Serhat; Baş, Süleyman; Çelik, Mehmet; Temiz, Sibel; Özçelik, Melike; Güneş, Pembegül; Cengiz, Hasret; Tütüncü, Yasemin; Ilıksu Gözü, Hülya (Journal of Surgery and Medicine, 2019)
Aim: Primary hyperparathyroidism (PHPT) is a clinical presentation of hypercalcemia resulting from autonomous excessive parathyroid secretion from parathyroid glands. Significant correlation between serum parathyroid hormone (iPTH), calcium (Ca), phosphorus (P) and 25-OH D3 levels and adenoma volume, have a predictive value to determine the size of parathyroid adenoma resection. In this study, we examined the relation between preoperative biochemical parameters and resected parathyroid adenoma volume. Methods: Fifty-two patients with PHPT diagnosed in the endocrinology outpatient clinic of Istanbul Haydarpaşa Numune Research Hospital, between 2011 and 2014 were included in the study. Histopathological diagnosis of solitary parathyroid adenomas was made. Correlation analysis was performed between adenoma volume and preoperative serum iPTH, corrected Ca, P, 25-OH D3 and 24 hour urinary calcium levels. The study was designed a cross-sectional study. Results: Fifty-two patients studied, 45 were female and 7 were male. The mean age of the patients was 53.538 ± 14.996 years. The mean preoperative iPTH level was 371.423 ± 341.8 pg / dl, corrected Ca level was 11.652 ± 0.947 mg / dl, phosphorus level was 2.285 ± 0.434 mg / dl and 25-OH D3 level was 11.442 ± 6.120 ng /dl. The calculated parathyroid adenoma volume averaged 1.612 ± 2 cm3. Correlation between parathyroid adenoma volume with parathormone levels and 24 hour urine calcium levels was positive whereas 25-OH D3 levels were negatively correlated with adenoma volume. Conclusion: The adenoma size correlates with iPTH and vitamin D levels in PHPT patients. These levels may have predictive value about adenoma volume.